Management of Respiratory Syncytial Virus Bronchiolitis: 2015 Survey of Members of the European Society for Paediatric Infectious Diseases - Elliott J. Carande; Andrew J. Pollard; Simon B. Drysdale (Canadian Journal of Infectious Diseases and Medical Microbiology, 2016)
In 1995, the European Society for Paediatric Infectious Diseases (ESPID) carried out a survey of its members to assess the variation in management of respiratory syncytial virus (RSV) bronchiolitis. The aim of the current study was to carry out a similar survey 20 years later to assess how the management had changed. An electronic, structured, English language survey, based on the United Kingdom National Institute for Health and Care Excellence (NICE) bronchiolitis draft guideline, was sent to ESPID members in March 2015. Questions asked included information on treatment practices of infants with bronchiolitis and doctor demographics. We received responses from 135 doctors (14% of the ESPID members) who worked in 115 hospitals. 56% of the doctors used a written guideline to manage bronchiolitic infants. All doctors stated that they isolated individually or in cohorts all hospitalised bronchiolitis infants. The level of oxygen saturation suggested as an indication to administer supplemental oxygen varied between <89% and <95%. We found significant reductions in the use of ribavirin, bronchodilators, and corticosteroids from 1995 to 2015 (ribavirin 57% to 13%, P<0.0001; bronchodilators 95% to 82%, P=0.0024; corticosteroids 81% to 45%, P<0.0001). Although variability in management remains high, encouragingly significantly fewer doctors are prescribing ribavirin, bronchodilators, and corticosteroids compared to 20 years ago.